Pengembangan Media Pembelajaran Fisika Dengan Macromedia Flash Untuk Melatihkan Penerapan Konsep Siswa SMP - Azhari, Andy; Mastuang, Mastuang; M., Abdul Salam (Berkala Ilmiah Pendidikan Fisika, 2017)
This study is base on the low of mediaâs aplicability. But actually in the case is mediasâ aplicability can help teacher to drill the studentsâ aplication concept. The purpose of this study is to produce physich learningâs media that suitable to use in drilling studentsâ aplication concept. The specific purfose of this study are (1) to describe the validity of physich learningâs media, (2) to discribe the practically of physich learningâs media based on lesson plan implementation during physics learning process, (3) to describe effectiveness of physich learningâs media based on studentsâ result test. This research and development used ASSURE (Analyze learner, state objectives, slect modify or design materials, utilize materials,require learner response and evaluate) design. The product result from this study is physich learningâs media with macromedia flash about optics. The study shows that: (1) The validity of learning media is categorized as good validity with a little correction, (2) the practically of learning media based on lesson plan implementation during physics learning process is categorized as practical, and (3) efectiveness of learning media based on studentsâ result test is categorized as effective. The conclusion of this research and development is physich learningâs media with macromedia flash is suitable to use in drilling the studentsâ aplication concept.Â Â